Answer:
x - ( 2 + 1 1/3)
=x- 3 1/3
- 3 1/3 feet
The water level of a pond falls 3 1/3 feet below its normal level.
Explanation:
The water level of a pond is 2 feet below its normal level.
The water level of the pond dropped another 1 1/3 feet.
So the total level dropped is 2 + 1 1/3
= 2 + 4/3
= 6+4/3= 10/3 = 3 1/3 feet below the normal.
Suppose the normal is at zero then the level of the pond is at the end of the summer is 0 - 3 1/3 = - 3 1/3 feet.
If we represent the normal by x then the equation becomes
x- 3 1/3 feet to show the water level at the end of summer.
Or it can also be written as
x - ( 2 + 1 1/3)